Ajulemic acid exerts potent anti-fibrotic effect during the fibrogenic phase of bleomycin lung. Issue 1 (December 2016) - Lucattelli, Monica; Fineschi, Silvia; Selvi, Enrico; Garcia Gonzalez, Estrella; Bartalesi, Barbara; De Cunto, Giovanna; Lorenzini, Sauro; Galeazzi, Mauro; Lungarella, Giuseppe
Abstract Background Ajulemic acid (AjA) is a synthetic analogue of tetrahydrocannabinol that can prevent and limit progression of skin fibrosis in experimental systemic sclerosis. In this study we investigated whether AjA also prevents and modulates lung fibrosis induced by bleomycin (BLM) when administered in mice during the inflammatory or the fibrogenic phase of the model. Methods The anti-inflammatory and antifibrotic efficacy of AjA was evaluated in DBA/2 mice treated orally once a day starting either at day 0 (preventive treatment) or at day 8 (therapeutic treatment) after a single intratracheal instillation of BLM. AjA was given at a dose of 1 mg/kg or 5 mg/kg. Mice were sacrificed at day 8, 14 and 21 after BLM and lungs were processed for histology and morphometry, and examined for HO-proline content and for the expression of transforming growth factor beta 1 (TGF-β1), phosphorylated Smad2/3 (pSMAD2/3), connective tissue growth factor (CTGF), alpha-smooth muscle actin (α-SMA) and peroxisome proliferator-activated receptor-gamma (PPAR-γ). Results In the 1st week after BLM challenge, an acute inflammation characterized by neutrophil and macrophage accumulation was the main change present in lung parenchyma. The "switch" between inflammation and fibrosis occurs between day 8 and 14 after BLM instillation and involves the bronchi and vasculature. In the subsequent week (at day 21 after BLM instillation) bronchiolocentric fibrosis with significant increase of tissue collagen develops. The fibrotic response evaluated by morphometry and quantified as HO-proline in lung tissue at day 21 after BLM treatment was significantly reduced in mice receiving either AjA in the inflammatory or in early fibrogenic phase. AjA induces marked change in the expression pattern of products implicated in fibrogenesis, such as TGF-β1, pSMAD2/3, CTGF and α-SMA. In addition, AjA increases significantly the number of PPAR-γ positive cells and its nuclear localization. Conclusions AjA treatment, starting either at day 0 or at day 8 after BLM challenge, counteracts the progression of pulmonary fibrosis. The anti-fibrotic effectiveness of AjA is irrespective of timing of compound administration. Further clinical studies are necessary to establish whether AjA may represent a new therapeutic option for treating fibrotic lung diseases.